Human α-synuclein-harboring familial Parkinson's disease-linked Ala-53 → Thr mutation causes neurodegenerative disease with α-synuclein aggregation in transgenic mice - Lee, Michael K. (National Academy of Sciences, 2002)
Mutations in α-synuclein (α-Syn) cause Parkinson's disease (PD) in a small number of pedigrees with familial PD. Moreover, α-Syn accumulates as a major component of Lewy bodies and Lewy neurites, intraneuronal inclusions that are neuropathological hallmarks of PD. To better understand the pathogenic relationship between alterations in the biology of α-Syn and PD-associated neurodegeneration, we generated multiple lines of transgenic mice expressing high levels of either wild-type or familial PD-linked Ala-30 → Pro (A30P) or Ala-53 → Thr (A53T) human α-Syns. The mice expressing the A53T human α-Syn, but not wild-type or the A30P variants, develop adult-onset neurodegenerative disease with a progressive motoric dysfunction leading to death. Pathologically, affected mice exhibit neuronal abnormalities (in perikarya and neurites) including pathological accumulations of α-Syn and ubiquitin. Consistent with abnormal neuronal accumulation of α-Syn, brain regions with pathology exhibit increases in detergent-insoluble α-Syn and α-Syn aggregates. Our results demonstrate that the A53T mutant α-Syn causes significantly greater in vivo neurotoxicity as compared with other α-Syn variants. Further, α-Syn-dependent neurodegeneration is associated with abnormal accumulation of detergent-insoluble α-Syn.